2014
DOI: 10.1167/iovs.14-13894
|View full text |Cite
|
Sign up to set email alerts
|

Macular Measurements Using Spectral-Domain Optical Coherence Tomography in Chinese Myopic Children

Abstract: Our study highlights the variations and sex differences of macular thickness/volume in Chinese myopic children using SD-OCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
34
3
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 37 publications
6
34
3
3
Order By: Relevance
“…We repeated each of the LMM analyses, using baseline axial length as a factor instead of refractive error group, and found similar trends of statistically significant associations between axial length and retinal thickness, indicating that the topographical changes in thickness associated with myopia are related to the increased axial length of myopic eyes. Although not a universal finding [12,13], previous studies using SD-OCT have also noted a thinning of the total retina in the parafoveal and/or the perifoveal region associated with myopia in childhood of similar magnitude to that found in the current study [14,19]. …”
Section: Discussionsupporting
confidence: 79%
“…We repeated each of the LMM analyses, using baseline axial length as a factor instead of refractive error group, and found similar trends of statistically significant associations between axial length and retinal thickness, indicating that the topographical changes in thickness associated with myopia are related to the increased axial length of myopic eyes. Although not a universal finding [12,13], previous studies using SD-OCT have also noted a thinning of the total retina in the parafoveal and/or the perifoveal region associated with myopia in childhood of similar magnitude to that found in the current study [14,19]. …”
Section: Discussionsupporting
confidence: 79%
“…Recent studies have reported that the foveal thickness of myopic patients is thicker than that in emmetropia patients and increases with progression of myopia [43, 44]. Although the present study showed no significant differences of foveal thicknesses, because there was no significant difference in myopia, parafoveal retinal thickness was associated with β -PPA, which may be attributed in part to the difference in mGCIPL thicknesses.…”
Section: Discussioncontrasting
confidence: 73%
“…Recent studies using OCT have shown that the fovea is thicker in myopic eyes [43, 45]. Several studies have hypothesized that the increased axial length causes mechanical stretching of the sclera at the posterior pole.…”
Section: Discussionmentioning
confidence: 99%
“…As established through OCT imaging, there is a significant negative correlation between axial length and retinal thickness . Chen et al deduced that despite the tendency for a slightly greater foveal thickness, Chinese children with moderately‐to‐highly myopic eyes had a decreased average macular thickness and volume in comparison with emmetropic children. The perifoveal area has been established as the zone of greatest thinning in myopic children .…”
Section: Interpretation Of Paediatric Oct Imaging: Normative Datamentioning
confidence: 99%
“…Chen et al deduced that despite the tendency for a slightly greater foveal thickness, Chinese children with moderately‐to‐highly myopic eyes had a decreased average macular thickness and volume in comparison with emmetropic children. The perifoveal area has been established as the zone of greatest thinning in myopic children . Similarly, OCT analysis of RNFL thickness of 104 children in Hong Kong showed a significant inverse relationship with the axial length of the eye .…”
Section: Interpretation Of Paediatric Oct Imaging: Normative Datamentioning
confidence: 99%